EKSISTENSI PANCASILA SEBAGAI SUMBER SEGALA SUMBER HUKUM DALAM KONSTITUSI INDONESIA - Sholikul Hadi (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
The Pancasila formula has been contained in the constitution that has been in effect in Indonesia, starting with Undang-Undang Dasar Negara Republik Indonesia 1945, Undang-Undang Dasar Republik Indonesia Serikat, Undang-Undang Dasar Sementara 1950. Nevertheless, the terms "Pancasila" and Pancasila as the source of all legal sources are not regulated in the constitution. Such provisions will affect the normal conflict in view that pancasila has been agreed upon as the source of all Indonesian legal sources. It aims to do a critical analysis of the existence of pancasila in the constitution in force in Indonesia since 1945 and the need for inclusion of the terms "pancasila" and "pancasila as the source of all law" in the constitution in Indonesia.